2020
DOI: 10.1109/tvt.2020.2985289
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Timescale Approach for Network Slicing in C-RAN

Abstract: Network slicing is a promising technique for cloud radio access networks (C-RANs). It enables multiple tenants (i.e., service providers) to reserve resources from an infrastructure provider. However, users' mobility and traffic variation result in resource demand uncertainty for resource reservation. Meanwhile, the inaccurate channel state information (CSI) estimation may lead to difficulties in guaranteeing the quality of service (QoS). To this end, we propose a two-timescale resource management scheme for ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…Slice admission and bandwidth allocation were performed on a long timescale, and the operator generated beamformers on each short timescale. To achieve efficient resource utilization, some investigations have been conducted to design the resource reservation and intraslice resource allocation from the perspective of the system [34,35]. In [34], a network slicing game was proposed to make a resource reservation with the aim of maximizing its user utility.…”
Section: Service Provisioning For Ran Slicingmentioning
confidence: 99%
“…Slice admission and bandwidth allocation were performed on a long timescale, and the operator generated beamformers on each short timescale. To achieve efficient resource utilization, some investigations have been conducted to design the resource reservation and intraslice resource allocation from the perspective of the system [34,35]. In [34], a network slicing game was proposed to make a resource reservation with the aim of maximizing its user utility.…”
Section: Service Provisioning For Ran Slicingmentioning
confidence: 99%
“…In this work, we consider slicing requests from eMBB and URLLC, two major application scenarios of 5G and beyond wireless network systems, and the bandwidth and computing resources required by URLLC slices and eMBB slices are denoted by b u , s u , b e and s e , and the computing resources leased from remote cloud servers is denoted by s c t . To cater the dynamic of the slice requests in practice, the timeslotted model is considered here, where time is divided into long time slots (LTSs) and short time slots (STSs) [12]. We denote LTS as L, and each LTS contains n STSs, denoted as L = (t 1 , t 2 , ..., t n ).…”
Section: System Modelmentioning
confidence: 99%
“…It is observed that although the expected outage is separable in r p k , variables are coupled in the first term of the objective function. Therefore, we substitute the global quadratic upperbound given in (21)…”
Section: A Resource Reservation In the Backhaulmentioning
confidence: 99%
“…Therefore, the Lipschitz constant is |P k |. We now place the Lipschitz constant in (21) and find the upper-bound which is separable in r p k as follows:…”
Section: A Resource Reservation In the Backhaulmentioning
confidence: 99%